ANALISIS POTENSI DAYA SAING PEMASARAN PRODUK UNGGULAN PISANG MAS KIRANA - Nawangsih, Nawangsih (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2018)
The horticultural development program in East Java aimed at increasing the production and quality of competitive superior products, developing products to support food diversification, promoting regional and national economic development, opening up to work employment opportunities, increasing foreign exchange income and farmers' and welfare. Banana is one of the leading horticultural products in Indonesia developed intensively to support the central government program in agriculture in sustainable development. Lumajang regency, one of the areas of banana-producing centers, produce various types of bananas of good quality. The research objectives are: to analyze the competitiveness potential of banana mas kirana product either competitively or comparatively and to know marketing strategy (4P) banana mas kirana superior product. Research methods is descriptive with qualitative approach. Technique of collecting data using interview, observation and documentation, sampling technique using purposive sampling, where informant research determined based on criterion in accordance with have been determined. Data analysis used stages consisting of: data collection, data reduction, data presentation, verification and conclusion. The result of the research shows that the competitiveness potential of kirana gold product is competitive or comparative is big enough, but there are still some things that need to be improved especially in terms of hatchery and processing that is still not standard among farmers. While the marketing strategy of 4P has been applied well, so that the superior product of banana mas kirana is favored and can be accepted by the consumers both from local and national, and become one of superior product from Lumajang Regency